Vocational education and Training in Slovenia : short description - (:unkn) unknown (Office for Official Publications of the European Communities, 2008)
This overview of vocational education and training (VET) in Slovenia has been produced to mark Slovenia's Presidency of the Council of the EU. It forms part of the series of short descriptions regularly published by Cedefop on national VET systems. The report sums up the main features of the Slovenian VET system as it stands at this stage of the reform process (December 2007). It describes the country's institutional and educational background and recent developments in VET (quality, permeability, recognition of nonformal and informal learning, individualisation and flexibility, attractiveness and governance). Particular features of the Slovenian VET system, such as the training of VET teachers and trainers, the role of the social partners, and the system of guidance and counselling, are also presented. (BIBB-Doku)
Keywords: S System beruflicher Bildung; S 2.3 Berufsbildungspolitik; I 2.2.2 Osteuropa; Berufsbildungssystem; Bildungspolitik; Berufsbildendes Schulwesen; Berufliche Weiterbildung; Bildungspersonal; Berufliche Qualifikation; Anerkennung; Informelles Lernen; Berufsberatung; Bildungsfinanzierung; Slowenien